The road to Tahrir Square : Egypt and the United States from the rise of Nasser to the fall of Mubarak - Gardner, Lloyd C., 1934- (New York, NY : New Press : Distributed by Perseus Distribution, 2011)
'The story of the United States' intimate and pivotal relationship with the Arab world's largest nation over the course of six decades'--Provided by publisher.
Includes bibliographical references (p. [207]-222) and index.
Keywords: United States -- Foreign relations -- Egypt; Egypt -- Foreign relations -- United States; United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- 1989-; Egypt -- Foreign relations -- 1952-